Efeito do treinamento físico combinado sobre o remodelamento vascular pulmonar em modelo experimental de hipertensão arterial pulmonar - Ferreira, Marília Sousa (2023)
Introduction: Pulmonary arterial hypertension (PAH) is a serious and progressive condition characterized by dramatic remodeling of pulmonary arteries and arterioles. These changes result in a progressive increase in pulmonary vascular resistance (PVR), leading to overload on the right ventricle (RV) and, consequently, to death. Combined exercise training (ET), which combines aerobic and resistance protocols, is widely used in rehabilitation services for PAH patients; however, its effects on structural changes in pulmonary vasculature in PAH remain unknown. Objective: This study investigated the effect of moderate-intensity combined aerobic and resistance ET on indicators of pulmonary vascular remodeling in an experimental model of PAH induced by monocrotaline (MCT). Methods: To test these hypotheses, Wistar rats (250-300g) received subcutaneous injection of MCT (40 µg/kg body weight) or saline. They were divided into groups subjected to 4 weeks of combined ET: MCT-T (aerobic: 40-60% Velmax, 3x/week; resistance: 40-60% Wmax, 2x/week) or sedentary groups: MCT-S and SAL-S. Arteriolar medial layer thickness and total perivascular collagen deposition were used as markers of pulmonary vascular remodeling. Results: The PAH model led to an increase in the thickness of the medial layer of pulmonary arterioles and similar levels of perivascular collagen compared to the healthy group. On the other hand, ET prevented medial layer remodeling and reduced total perivascular collagen deposition in animals with PAH (MCT-T) compared to sedentary groups. These original findings reinforce the beneficial effect of combined ET in preventing early vascular changes in PAH.